Finite-element analysis-based design and efficacy assessment of a three-dimensional anisotropic heel cushioning pad for diabetic foot management - Yang, Xiong-Gang; Hu, Xing-Xi; Ma, Lang-Tao; Jiang, Ming-Qi; Zhang, Gui-Qian; Lu, Sheng (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDiabetic foot ulcer (DFU) is a common complication observed in diabetic patients, which can lead to lower limb amputation in severe cases and seriously impair the patient’s mobility and even endanger life. Plantar insoles aim to redistribute pressure, yet diabetic foot tissues exhibit altered material properties, necessitating a novel approach to address vertical pressures and shear forces. This study sought to design a three-dimensional anisotropic heel cushioning pad that mitigates both vertical pressure and anteroposterior/mediolateral (AP/ML) shear forces.MethodsCT data of the foot were collected and stored in DICOM format. We reconstructed a foot model and simulated the heel cushioning pad with varying elastic moduli in compressive, AP-shear, and ML-shear directions. We used finite-element analysis (FEA) to assess the impact of these moduli on peak stresses under various loading conditions. The data were fitted with a polynomial, and a regression equation was obtained.ResultsReducing the elastic moduli of heel cushioning pads led to decreased peak stresses across all directions. Notably, the peak compressive stress decreased by 52.20%–66.91%, while AP and ML shear stresses decreased by 51.05%–75.58% and 54.16%–72.42%, respectively. Polynomial analyses revealed optimal stress reductions within specific elastic modulus ranges (400, 800, and 1,000 kPa in compressive, AP-shear, and ML-shear dimensions, respectively), indicating diminishing benefits beyond these points.ConclusionFEA revealed that heel cushioning pads with tailored elastic moduli can significantly reduce peak stresses, with diminishing benefits observed beyond certain thresholds. These findings suggest that selecting materials with elastic moduli just before the plateau could yield the most effective cushioning for DFU prevention, offering valuable insights for industrial applications.